The narrative approach in Bioethics - Mario Picozzi (Hygeia Press di Corridori Marinella, 2015)
Nowadays, the narrative approach in Bioethics is more and more considered and used. In our paper we would like to explain why - when we need to take a decision - it is essential and crucial that the patient tells his own history; we also indicate the main consequences that this approach has with reference to the choices at the bed of the patient.   Selected Papers of the Congress "Narrative Based Medicine and Communication in Clinical Practice" · Cagliari, Italy · April 14th, 2014 Guest Editors: Massimiliano Zonza, Vassilios Fanos, Gian Paolo Donzelli